The Influence of the “Dine Out Deals” Discount Promotion and Visual Communication Design on Consumer Purchase Decisions in GrabFood Services at Sun Plaza Mall Medan with Purchase Intention as a Mediating Variable - Dian Natari; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Indonesian Journal Publisher, 2025)
The lower transaction value of GrabFood compared to its competitors raises questions about market dominance and the sustainability of the platform's growth. Visual communication design should help convey information, but the effectiveness of the